Factors Associated With Self-Reported Overdose Reversals Using Naloxone in Little Rock, Arkansas: Implications for Harm Reduction Service Delivery in the US South - Pro, George (Journal of drug issues, 2025)
Background. The Central Arkansas Harm Reduction Project (CAHR) is located in Little Rock, Arkansas, and is the only harm reduction service provider in the city. This quality improvement study was conducted to inform harm reduction programming decisions. Methods. We used CAHR data among clients who reported methamphetamine and/or opioid use (2021-2022; N = 459). We used an explanatory mixed methods design to identify factors associated with self-reported overdose reversals using naloxone. Results. The average number of reversals was 3.27. Nearly all clients (95%) reported methamphetamine use. The use of both methamphetamine and opioids (vs. opioids only; β = 0.26, p = .04) was positively associated with a higher number of reversals. Our qualitative analysis provided additional context around methamphetamine and overdose, including leveraging community members connected to large networks of people who use drugs. Conclusion. Future CAHR initiatives will focus on expanding public health education around naloxone and fentanyl for a population increasingly using methamphetamine.